Effects of using the GlobalFiler™ multiplex system on parent–child analyses of cases with single locus inconsistency. (January 2016) - Ochiai, Eriko; Osawa, Motoki; Tamura, Tomonori; Minaguchi, Kiyoshi; Miyashita, Keiko; Matsushima, Yutaka; Kakimoto, Yu; Satoh, Fumiko
Graphical abstract: Highlights: Advanced STR multiplex system was applied to parent–child analysis. Single inconsistency was detected in seven cases of 221 pairwise analyses. Inconsistency occurred at a higher rate than the conventional 15 loci system. Analysis of 21 loci improved the ability to infer the relation with inconsistency. Abstract: Parent–child analyses sometimes reveal inconsistency of shared alleles at only one locus. This is conventionally called "single locus exclusion", which results from mutational events and the presence of null alleles. Here, in parent–child analyses of the Japanese population, we detected exclusions by using the GlobalFiler™ system comprising 21 short tandem repeat loci. One- or two-step mutations resulting from strand slippage causing gain or loss were observed in seven of 221 parent–child transmissions. The incidences of single locus inconsistency of alleles were 5.88 × 10 −2 and 8.40 × 10 −3 for paternal and maternal relationships, respectively. With calculation using a set of 15 loci in the Identifiler® multiplex system, the combined likelihood ratio (CLR) values were limited to less than 100 in all five cases accompanied by single inconsistency. The addition of six loci recovered the CLR values to over 10, 000 in three cases. Application of this advanced system may increase the detected occurrence of mutational events, but it should be beneficial for inference in parent–child analyses, particularly in cases accompanied by genetic inconsistency.